Consumer purchase intention and behavior toward the online agricultural market - Narciso, Rafael Luis Z. (Animo Repository, 2021)
In recent years, many traditionally physical markets in the Philippines have been shifting towards digital and online platforms. One industry that is following the trend is the agricultural sector, wherein various online stores have opened to sell agricultural products. However, there is little information on the different factors that can entice consumers to shift from the traditional to the digital method in the buying of agricultural products. In this study, the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) model was utilized to determine which factors have significant effect on consumer online purchase behavior; moreover, it sought to determine if there would be moderating effects in terms of Age, Gender, Experience, and Willingness to Buy Local. A sample survey of 207 respondents with the age range of 21 - 40 years old and who are current residents of the Philippines were obtained for analysis. The analysis was done through a Structural Equation Model (SEM) to determine the relationships and effects of the indicating variables of the study with the latent variables. The results of the study showed that Facilitating Conditions, Price Value, and Habit were significant indicators of online purchase intention for agricultural products. Gender, Experience, and Willingness to Buy Local also had significant moderating effects on given independent variables of the study.